Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Pt. Global Ardhitya Swamandiri Jakarta Utara - Musa Bagus; Ratna Sari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This This study aims to determine the effect of work discipline and work motivation on employee performance at PT. Global Arditya Swamandiri, both partially and simultaneously. The method used in this study is a quantitative approach. The population in this research consists of 70 employees of PT. Global Arditya Swamandiri. The data collection technique was carried out using a sampling method called a saturated sampling technique, where the entire population was used as the sample. Thus, the research sample consisted of 70 respondents. The data analysis methods used in this study include instrument tests such as validity and reliability tests, classical assumption tests consisting of normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Furthermore, the analysis includes multiple linear regression tests, correlation coefficient tests, hypothesis tests (t-test for partial significance and F-test for simultaneous significance), and the coefficient of determination (R²) test. Based on the research results, it can be concluded that work discipline has a positive and significant effect on employee performance, as indicated by the value of t_calculated > t_table (9.320 > 1.676), supported by a significance value of 0.000 < 0.05. Therefore, H₀₁ is rejected and H₁ is accepted. Work motivation also has a positive and significant effect on employee performance, with a t_calculated value > t_table (9.291 > 1.676), supported by a significance value of 0.000 < 0.05. Thus, H₀₂ is rejected and H₂ is accepted. Work discipline and work motivation simultaneously have a positive and significant effect on employee performance, with an F_calculated value > F_table (62.230 > 3.183), and a significance value of 0.000 < 0.05. Hence, H₀₃ is rejected and H₃ is accepted.